EFEKTIFITAS OBAT PENURUN KOLESTEROL 'STATIN' DALAM MENURUNKAN KEJADIAN KARDIOVASKULER PADA SINDROM KORONER AKUT - -, Sajinadiyasa; Santoso, Anwar (journal of internal medicine; Vol. 9, No. 1 Januari 2008)
Acute coronary syndromes (ACS) is usually caused by atherosclerotic process in coronary artery. Clinical manifestation of ACS is unstable angina pectoris, acute miocard infarc ( non-Q-wave and Q-wave) and sudden death. ACS develop have various degrees of coronary artery occlusion. ACS is caused by rupture of plaque with a thin cap. Inflammation is also plays the pathogenesis these syndromes. Stable plaque is imfortance condition in prevent cardiac event and statin drug lowering cholesterol can made stable plaque and as antiimplammation.
Keywords: ACS, rupture plaque, statin